The influence of age on the phenolic contents and lignins of Gmelina arborea (Lamiaceae) - Azofeifa Bolaños, Jose Bernal; Álvarez Valverde, Víctor; Olivares Madriz, Ashly; Pineda Cascante, Mariana; Campos Salas, Daniela; Hine-Gómez, Ana (Revista de Biología Tropical, 2024)
Introduction: Melina (Gmelina arborea) is a tree species of great interest for its wood and medicinal properties. In Costa Rica, there are genetically superior clones that are propagated without knowledge of the ontogenic and physiological age of the materials. Objective: To evaluate how age influences the content of phenols and lignins in leaves, petioles, stems, and roots of melina plants. Methods: The total phenolic and lignins contents were determined using Folin-Ciocalteu colorimetric method and alkaline extraction method, respectively. Plants of five different ages were chosen for the investigation (in vitro plants “year 0” and trees of a year and a half, four, seven and 20 years). Sampling was done in March and April 2021. Results: All parts of the plant analyzed contain phenolic compounds and lignins, regardless of their age. There was no positive correlation between age and phenol and lignin content for any development condition, since the highest values were not obtained in the oldest trees. Leaf extracts from in vitro plants and seven-year-old trees showed, respectively, the highest phenol and lignin contents for all conditions (P < 0.05). The lowest average values of phenolic compounds for all conditions were obtained in four-year-old trees. Regarding lignins, the lowest content occurred in the oldest roots, although the trend was not maintained for the rest of the plant parts. Conclusions: This study provides the first results of the content of phenolic compounds and lignins present in different tissues of a forest species of different ages. Therefore, they are the first reference values about the biochemical commitment for phenolic synthesis according to the age and the specific developmental stage of a woody plant.